Manejo intraoperatório do sangramento em cirurgias de grande porte com métodos viscoelásticos - de queiroz, daniel vieira; Duran, Marcelo Sampaio; Cherman, Aline Alonso (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
Perioperative monitoring of blood clotting is essential to estimate the risk of bleeding, to diagnose coagulopathy, and to guide hemostatic therapies during surgical procedures. Assessment of hemostasis and the choice of blood products have traditionally been made based on conventional coagulation tests. However, these tests have limitations, as they have high turnaround times and evaluate only the beginning of the whole clot formation process. Viscoelastic tests are an adequate alternative to the use of traditional methods of hemostasis monitoring, as they allow a global assessment of blood clotting, from the beginning of thrombus generation to its dissolution, with fast point-of-care results. Rotational thromboelastometry is a viscoelastic test that has gained importance in the perioperative setting. The test shows a graphical representation of clot formation in real-time and provides a range of parameters about the structure and kinetics of clot formation. The main recommendations of use of this method include diagnosing complex coagulopathy and guiding the hemostatic therapy in the perioperative setting of major surgery, such as cardiac surgery, liver transplant, major trauma, and bleeding in critical patients. The objective of this study is to present an update on viscoelastic methods (focusing on rotational thromboelastometry) and their applicability in different clinical scenarios.